Variation of mean value of velocity of ion with different obliqueness of magnetized plasma sheath - Adhikari, B.R.; Lamichhane, H.P.; Khanal, R. (Himalayan Physics, 2020)
Plasma sheath, which forms between a material wall and incoming plasma, plays an important role in controlling particle and energy ﬂuxes to the wall. The problem of plasma sheath is one of the oldest in plasma and still draws attention, especially in magnetized plasmas. In this work velocity of ions in a magnetized plasma sheath has been studied using a kinetic trajectory simulation model for varying obliqueness of the ﬁeld. Any change in obliqueness of the ﬁeld causes the velocities to change. The change in mean value of the component normal to the wall is comparatively small whereas the other two components of velocity vary sinusoidally, nearly complementary to each other with nearly equal amplitudes.